Biopesticidal Activity of Cassava (Manihot esculenta Crantz) Seed Oil Against Bihar Hairy Caterpillar ( Spilarctia obliqua) and Cowpea Aphid (Aphis craccivora) - Jayaprakas, C. A; Ratheesh, S; Rajeswari, L. S (JOURNAL OF ROOT CROPS, 2014)
Cassava seed oil (CSO) from mature fruits of indigenous cassava (Manihot esculenta Crantz) varieties was extracted in petroleum ether (60-80 ºC). Gas chromatography studies on the lipid profile of the oil showed the presence of 13 fatty acids with dominance of C18 component (oleic). Other major components of the oil were stearic acid (19.61%) and myristic acid (10.73%). The oil was highly unsaturated and can be used as edible oil. The biopesticide property of the CSO was tested against aphids (Aphis craccivora) on cowpea and ivy gourd. The oil at 1 and 0.5% concentrations gave 100% mortality of the pest within 24 and 48 hours of treatment, respectively. Bioassay of CSO at 1% concentration against fourth instar larvae of Spilarctia (Spilosoma) obliqua (Bihar hairy caterpillar) resulted in 93.3% mortality in the larval population.